The bees of the genus Colletes Latreille 1802 of the Ukraine, with a key to species (Hymenoptera: Apoidea: Colletidae) - Proshchalykin, Maxim Yu.; Kuhlmann, Michael (Zootaxa, 2012)
Twenty two species of the bee genus Colletes are recorded for Ukraine and C. brevigena Noskiewicz 1936 is reported for the first time. A new synonymy is here established: C. maidli Noskiewicz 1936 = C. lebedewi Noskiewicz 1936, syn. nov. The patterns of the zonal distribution of Colletes in Ukraine are discussed. Original illustrated keys to males and females of all species known from Ukraine are provided.